2015
DOI: 10.1002/jts.22060
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress among Victimized Latino Women: Evaluating the Role of Cultural Factors

Abstract: Research examining victimization and posttraumatic symptomatology among Latinos is lacking in the extant literature. This analysis used the victimized subsample (N = 752) of the Sexual Assault Among Latinas Study. The aim was to evaluate victimization prevalence and test the following hypotheses: (a) that victimization would be associated with higher levels of posttraumatic symptoms, (b) that cultural factors that move away from traditional Latino culture would be associated with higher levels of posttraumatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…Consistent pattern of associations was found in the case of negative religious coping and symptoms of disorders: depression (Ahrens et al, ; Henslee et al, ; Leaman & Gee, ), PTSD (Berzengi, Berzenji, Kadim, Mustafa, & Jobson, ; Cuevas et al, ; Currier et al, ; Gerber et al, ; Harris et al, ; Leaman & Gee, ; McCann & Webb, ; Park et al, ; Raines et al, ; Wortmann et al, ; Zukerman, Korn, & Fostick, —only in women; Zukerman, Korn, Shapiro, & Fostick, , avoidance symptoms), distress (Chan & Rhodes, ), suicidal ideations (Currier, Smith, & Kuhlman, ; Kopacz et al, ; Raines et al, ), and substance use (Raines et al, ). Lack of significant associations between the negative coping and symptoms of PTSD was demonstrated in Ahrens et al (), Al‐Hadethe et al (), and Chan and Rhodes ().…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Consistent pattern of associations was found in the case of negative religious coping and symptoms of disorders: depression (Ahrens et al, ; Henslee et al, ; Leaman & Gee, ), PTSD (Berzengi, Berzenji, Kadim, Mustafa, & Jobson, ; Cuevas et al, ; Currier et al, ; Gerber et al, ; Harris et al, ; Leaman & Gee, ; McCann & Webb, ; Park et al, ; Raines et al, ; Wortmann et al, ; Zukerman, Korn, & Fostick, —only in women; Zukerman, Korn, Shapiro, & Fostick, , avoidance symptoms), distress (Chan & Rhodes, ), suicidal ideations (Currier, Smith, & Kuhlman, ; Kopacz et al, ; Raines et al, ), and substance use (Raines et al, ). Lack of significant associations between the negative coping and symptoms of PTSD was demonstrated in Ahrens et al (), Al‐Hadethe et al (), and Chan and Rhodes ().…”
Section: Resultsmentioning
confidence: 68%
“…McIntosh, Poulin, Silver, and Holman () measured both religiosity (institutionally related practices) and spirituality (subjective, personal beliefs); at least six other papers distinguished between the institutional religious practice and spirituality. However, some of the papers did not make a clear distinction between those two terms (i.e., Brooks, Lowe, Graham‐Kevan, & Robinson, ; Cuevas, Sabina, & Picard, ; López, Camilli, & Noriega, ). Religious practices such as prayer or service attendance were assessed through self‐report in 18 papers (although some scales assessing general religiosity also contained subscales referring to behavior/practices, so this number could be higher).…”
Section: Resultsmentioning
confidence: 99%
“…Acculturation and enculturation were measured using the Brief-ARSMA-II, an instrument that assesses both majority and minority cultural identity (Bauman, 2005) and includes items from the complete ARMSA-II (Cuéllar, Arnold, & Maldonado, 1995). Although these questions measure an individual’s Anglo orientation and Mexican orientation, none of the questions specifically refer specifically to Mexican culture, and the instrument has been successfully used with the Latino population in general (hence, we have used the term Latino Orientation in the past; Cuevas, Sabina, & Picard, 2015). Here we refer to Anglo Orientation as ‘Acculturation’ and Mexican Orientation as ‘Enculturation’.…”
Section: Methodsmentioning
confidence: 99%
“…Other research, however, indicates that having a higher Latino cultural identity may buffer the negative mental health effects of IPV on Latinas (Cuevas et al 2012a). For example, one study found that higher Latino cultural values and beliefs served as a protective factor against PTSD (Cuevas et al 2015). This research has begun to help us understand the various ways that Latinas experience negative consequences due to IPV and intersecting factors that can buffer or exacerbate these experiences.…”
Section: Consequences Of Ipv Exposurementioning
confidence: 99%